Short term ex-vivo expansion of circulating head and neck tumour cells - O'BYRNE, KEN (My University, 2016)
Minimally invasive techniques are required for the identification of head and neck cancer (HNC) patients who are at an increased risk of metastasis, or are not responding to therapy. An approach utilised in other solid cancers is the identification and enumeration of circulating tumour cells (CTCs) in the peripheral blood of patients. Low numbers of CTCs has been a limiting factor in the HNC field to date. Here we present a methodology to expand HNC patient derived CTCs ex-vivo. As a proof of principle study, 25 advanced stage HNC patient bloods were enriched for circulating tumour cells through negative selection and cultured in 2D and 3D culture environments under hypoxic conditions (2% O2, 5% CO2). CTCs were detected in 14/25 (56%) of patients (ranging from 1–15 CTCs/5 mL blood). Short term CTC cultures were successfully generated in 7/25 advanced stage HNC patients (5/7 of these cultures were from HPV+ patients). Blood samples from which CTC culture was successful had higher CTC counts (p = 0.0002), and were predominantly from HPV+ patients (p = 0.007). This is, to our knowledge, the first pilot study to culture HNC CTCs ex-vivo. Further studies are warranted to determine the use of short term expansion in HNC and the role of HPV in promoting culture success.
Keywords: head and neck cancer (HNC); head and neck cancer (HNC)